Adherence to treatment and level of control among asthma patients at a Lima hospital - Rodriguez-Marino , J. (2021)
Objective: Describe the association between asthma control and adherence to treatment in patients of the Hospital Nacional Dos de Mayo 2019-2020. Materials and methods: A quantitative, descriptive and retrospective clinical study was carried out during the 2019-2020 period in asthmatic patients from the Hospital Nacional Dos de Mayo (HNDM). The relationship between control and adherence to treatment in patients seen in the Asthma office of the Pneumology Service was evaluated by collecting data: Inhaler adherence test (TAI), Asthma control test (ACT) age, sex, treatment established, time of illness and nutritional assessment, through the review of medical records. Statistical analysis was performed with IBM SPSS Statistics version 22 software and the chi-square statistical test was performed to determine the association. Results: 187 patients were evaluated through medical records, 84 men (44.9%) and 103 women (55.1%). The mean age was 59.42 ± 15.08 (considering only adults). Through the analysis of the data from the medical records were determined, 86 controlled patients (46%), 48 patients are adherent (25.7%), the most used type of treatment is inhaled corticosteroid (ICS) with 50.8%, type of non-compliant more frequent is the unconscious (64.2%), the mean time of illness was 21.78 ± 16.75. Conclusions: In conclusion, we can say that, of the patients with adherence, 75% are controlled.